2021
DOI: 10.1016/j.cub.2021.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA reveals links between abundance and composition of airborne grass pollen and respiratory health

Abstract: Environmental DNA reveals links between abundance and composition of airborne grass pollen and respiratory health Highlights d Airborne grass pollen assemblages are quantitatively structured in space and time d The respiratory health impacts of grass pollen may vary according to grass species

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Our study adds to the growing body of evidence that nuclear markers are well suited for quantitative molecular pollen research ( Banchi et al, 2020 ; Nunez et al, 2017 ; Richardson et al, 2021 ; Rowney et al, 2021 ). The correlation values for all taxa using trn L and nrITS2 in this study are very similar to those found in a recent study on bee-collected pollen quantification ( Richardson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our study adds to the growing body of evidence that nuclear markers are well suited for quantitative molecular pollen research ( Banchi et al, 2020 ; Nunez et al, 2017 ; Richardson et al, 2021 ; Rowney et al, 2021 ). The correlation values for all taxa using trn L and nrITS2 in this study are very similar to those found in a recent study on bee-collected pollen quantification ( Richardson et al, 2021 ).…”
Section: Discussionmentioning
confidence: 64%
“…As an alternative to morphological pollen identification, DNA metabarcoding has been shown to provide increased taxonomic resolution and it has been used successfully on bee-collected pollen ( Bänsch et al, 2020 ; Elliott et al, 2021 ; Gous et al, 2021 ; Richardson et al, 2019 ) as well as airborne pollen ( Banchi et al, 2020 ; Brennan et al, 2019 ; Campbell et al, 2020 ; Kraaijeveld et al, 2015 ; Uetake et al, 2021 ). For grasses (Poaceae) for example, a recent study has shown that pollen of a small subset of all species present in the UK is likely to have a disproportionate influence on human health ( Rowney et al, 2021 ). However, such highly detailed information is not yet available for other plant families.…”
Section: Introductionmentioning
confidence: 99%
“…The model was increasingly used in various authoritative studies in different fields including ecology, biology, and human clinical research. 17 , 18 A novel model was adopted to analyze the relationship between the combination of muscle-fat and bone health in our study. In our study, the results of GAMs suggested that the relationship of fat and muscle on BMD was not one-way linear ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…While most research has focused on bacteria, microalgae (Tesson et al 2016) and fungi have also been explored (Fröhlich-Nowoisky et al 2012). Plant pollen is intensively studied for its allergenic potential and public health implications and metabarcoding is starting to be used for its identification (Kraaijeveld et al 2014; Brennan et al 2019; Rowney et al 2021). Fungal spores were targeted for biodiversity monitoring of the regional fungal community (Abrego et al 2018; 2020) and are currently being evaluated worldwide in the Global Spore Sampling Project (Ovaskainen et al 2020).…”
Section: Introductionmentioning
confidence: 99%